ENHANCING CRITICAL READING SKILLS IN STUDENTS: STRATEGIES AND APPROACHES (Yangi O'zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2024)
This article delves into enhancing critical reading skills, emphasizing strategies like active highlighting and margin notes for improved annotation. It advocates for questioning techniques and comparative analysis to develop analytical thinking. The importance of engaging with diverse texts, utilizing technology, and various assessment strategies are explored, concluding with the promotion of a reading culture through literature circles and author workshops.